Method to simultaneously measure 3D kinematic and kinetic data during normal level walking using KISTLER force plates, VICON System and videofluoroscopy - Gerber, H.; Zihlmann, M.; Foresti, M.; Stüssi, E. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
Force (kinetic) and opto-electrical motion tracking (kinematic) measuring techniques are well established to analyse gait and other movement patterns. During the last years, videofluoroscopy became a new and well accepted technique to get accurate kinematic information of artificial joints in vivo by a three dimensional numerical reconstruction of the single plane projection view of fluoroscopic images. The method presented allows to simultaneously acquiring kinetic and kinematic data with KISTLER force plates, VICON system and a moving videofluoroscopic system during normal level walking. This new combination of measuring techniques allows an improved analysis of load and movement of the human body.